225k views
0 votes
Which of the following expressions demonstrates the distributive property? 3 + 4 + 5 = 4 + 3 + 5 -2(5 + 7) = -2(7 + 5) 3(-8 + 1) = 3(-8) + 3(1) 6[(7)(-2)] = [(6)(7)](-2)

User BPS
by
5.4k points

2 Answers

6 votes

AWNSER

C, 3(-8 + 1) = 3(-8)

Explanation:

User Jeffrey Berthiaume
by
5.4k points
4 votes

Answer:


3(-8+1)=3(-8)+3(1)

Explanation:

In the above choice, the 3 is being multiplied – or distributed – to the values within the parentheses. Recall that the distributive property says:


a(b+c)=ab+ac

User Badr
by
5.6k points